2006
DOI: 10.1007/s11062-006-0021-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological parameters of mauthner neurons of goldfishes with modified asymmetry of motor behavior

Abstract: We examined the morphological peculiarities of Mauthner neurons, MNs, in goldfishes with a phenotypically different or an experimentally modified preference to perform rightward vs leftward turnings in the course of motor behavior; this preference was characterized by values of the motor asymmetry coefficient (MAC). 3D reconstruction of MNs was performed based on several histological sections; volumes of the soma, lateral and ventral dendrites (LD and VD, respectively), initial segment of the axon, as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…Adaptation using bilateral stimulation was induced using the protocol described earlier [14]. To test the level of adaptational changes in one of the MNs, we used both bilateral and contralateral (with respect to a dominant MN) vestibular stimulation using the technique developed earlier [9,11].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adaptation using bilateral stimulation was induced using the protocol described earlier [14]. To test the level of adaptational changes in one of the MNs, we used both bilateral and contralateral (with respect to a dominant MN) vestibular stimulation using the technique developed earlier [9,11].…”
Section: Methodsmentioning
confidence: 99%
“…They are, to a considerable extent, determined, on the one hand, by the morphofunctional asymmetry of MNs that is manifested in behavior as the motor asymmetry of the fish [7,8] and, on the other hand, by variations of this asymmetry depending on the preceding loading on one afferent input or another. It was found that experimental adequate stimulation or unilateral elimination of one input selectively influences the structure and function of the individual MN; this leads to a change in the inborn motor asymmetry of the fish [9,10]. Regulation of all the above modifications at the level of the individual MN has not at present been studied.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain 3-D reconstructions (images) of MNs and to estimate the dimensions of the right and left neurons, we used the technique described earlier [19]. Serial 3-µm-thick sections of the medulla were studied using a light microscope provided with a digital camera.…”
Section: Methodsmentioning
confidence: 99%
“…The true volume of the MNs was estimated as the sum of the volumes of these three main (greatest) components (taking into account a preliminary calculated coefficient of compression of the tissue). Alignment of images of the medulla sections with respect to each other and 3-D reconstruction of the MNs were performed using the corresponding computer software [19,20]. For electron microscopic studies, we prepared serial slices of the medulla (10 µm thick).…”
Section: Methodsmentioning
confidence: 99%
“…This is why many aspects of the functional role of the ventral dendrite of MNs remain unknown or have been studied to a much lesser extent than roles of the somatic part and of the lateral dendrite of the above cells. The existing data were obtained mostly in acute experiments with the use of a denervation technique [10,11].…”
Section: Introductionmentioning
confidence: 99%